2015
DOI: 10.1016/j.fuproc.2014.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Mercury speciation in liquid petroleum products: Comparison between on-site approach and lab measurement using size exclusion chromatography with high resolution inductively coupled plasma mass spectrometric detection (SEC-ICP-HR MS)

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 22 publications
1
29
1
Order By: Relevance
“…Background corrected 2 D map obtained from the experiment confirmed not only non-homogeneous distribution of the analyte but also formation of large Hg containing aggregates (Figure 3). In a recent study Gaulier, et al, 34 identified formed Hg aggregates as HgS particles using scanning electron microscope with energy dispersive spectroscopy. The average size of the particles was found to be 1 µm in diameter and the particles formed aggregates of 5 -10 µm in size.…”
Section: Hg Species Quantification By Species Specific Isotope Dilutimentioning
confidence: 99%
“…Background corrected 2 D map obtained from the experiment confirmed not only non-homogeneous distribution of the analyte but also formation of large Hg containing aggregates (Figure 3). In a recent study Gaulier, et al, 34 identified formed Hg aggregates as HgS particles using scanning electron microscope with energy dispersive spectroscopy. The average size of the particles was found to be 1 µm in diameter and the particles formed aggregates of 5 -10 µm in size.…”
Section: Hg Species Quantification By Species Specific Isotope Dilutimentioning
confidence: 99%
“…Hg in oil, air, and water is reported to occur as elemental Hg(0), and as a variety of Hg­(I) (mercurous) and Hg­(II) (mercuric) species depending on redox conditions. Each of these species will have a range of volatility, stability, and solubility in oil and in water that will affect its behavior in the oil and gas value chain. Thus, a better understanding of the mercury speciation of solids in crude oil and solid byproducts in the refining process is critical to (i) most efficiently manage byproducts to avoid the release of Hg and (ii) to the success of strategies used to remove mercury from crude oil, before it is shipped and refined, thereby collecting the Hg at the initial extraction stage rather than dispersing the Hg into the downstream processing .…”
Section: Introductionmentioning
confidence: 99%
“…Even though the sorption affinity of Hg−alkyl thiol was lower than that for dissolved Hg(II) species in water, it effectively removes Hg at concentrations that have been found in petroleum products. 56,57 A dose of 50 mg L −1 removed over 80% of the Hg−alkyl thiol in n-dodecane, when the initial mercury concentration was less than 2 mg L −1 with K d = 8.6 × 10 4 mL g −1 (Figure S5c). This is more than 100 times greater than the reported K d of thiol-functionalized porous silica material for removing ionic mercury species in oil.…”
Section: Resultsmentioning
confidence: 99%